Enhanced quantum yield of nitrogen fixation for hydrogen storage with in situ-formed carbonaceous radicals1. Issue 23 (21st March 2015) - Zhao, Weirong; Xi, Haiping; Zhang, Meng; Li, Yajun; Chen, Jinsheng; Zhang, Jing; Zhu, Xi
<x xml:space="preserve">Abstract</x> N2 can be reduced to NH3, a green hydrogen storage material, using suitable photocatalysts and scavengers under UV irradiation.